Mapping Micro-Level Decision-Making for Alligator Management in North Carolina - Cavalier, Rebecca; Serenari, Christopher; Konur, Dinçer (Frontiers in Conservation Science, 2021)
Human-carnivore interactions represent a grand challenge to conservation decision-making and legitimacy across all levels of governance. Human populations continue to encroach upon and devastate carnivore habitats and populations, intensifying interactions between a variety of biodiversity interests and beneficiaries. As a result, carnivores most intensely impact those living in their midst, demanding increased attention by local decision makers, who are often best suited to catering to the needs of communities most affected. Their views and desires can serve as a forerunner of public trust and acceptance of policies created. However, due to the complexity of decisions about carnivores, these actors are often overlooked in the formal decision process. To address this need, we applied multi-criteria decision analysis (MCDA) to a case study of American alligator (Alligator mississippiensis) conservation in 10 coastal North Carolina counties to identify and postulate legitimate outcomes. We surveyed 25 local decision makers who are or may be responsible for management decisions concerning the American alligator and asked them to evaluate and indicate the level of importance of salient alligator management elements. Results indicate that decision makers strongly favored the wildlife and social factors when making alligator management decisions, as well as the criteria human well-being, attitudes toward alligators, education programs, and storm mitigation. Respondents favored highly managed and balanced management alternatives to maximize preferred criteria and achieve legitimate alligator management at the local level. These results demonstrate that local decision makers are capable of identifying what is important to alligator management decisions, and can provide an insightful look at trade-offs that need to or could be made to achieve optimal alligator outcomes. We conclude that local decision makers should become more involved in shaping carnivore outcomes to enhance legitimacy of alligator policy and help achieve conservation targets. Future research will need to further expand understandings of local decision makers' decision-making process in other carnivore contexts. Researchers will want to consider using and refining decision analysis to cut through the complexity of carnivore conservation decision-making that exists across wide geopolitical expanses.